Single-cell RNA sequencing of shoot apex reveals the mechanism of cyclin regulating cell division via auxin signaling pathway in Populus alba - Liang, Jing-hui; Wu, Zhao-qun; Zhang, Yue-Xuan; Yang, Ye-Bo; Wang, Shi-Yi; Gai, Meng-Yu; Wang, Yu-Wen; Zhang, Xiu-Xing; Xue, Jing; Duan, Bo-Hao; Yang, Hai-Ling (Frontiers in Plant Science, 2025)
The shoot apex of Populus alba primarily comprises the shoot apical meristem, axillary meristem, leaf primordium, and young leaves, all of which exhibit high division potential. The single-cell RNA sequencing of the apical buds of P. alba can provide deeper insights into the processes of cell proliferation and differentiation, including the key genes and signaling pathways that regulate these processes. Scanning electron microscopy was used to examine the structure of the shoot apex, followed by single-cell sequencing analysis. A total of 29,011 cells were obtained from two biological replicates. Dimensionality reduction and clustering identified 17 distinct cell clusters. Pseudotime analysis revealed that shoot apex meristem cells and mesophyll cells emerged first, followed by the differentiation and maturation of vascular and intercalary meristem cells over time. Trichome differentiation occurred last, whereas epidermal cell differentiation persisted throughout development. At the single-cell level, auxin signaling pathway genes potentially involved in leaf tissue development were identified, along with an analysis of the expression specificity of CYC and CDK genes across mesophyll, epidermis, vascular, and shoot apex meristem tissues. These findings facilitate the elucidation of the molecular regulatory mechanisms by which CYC and CDK genes influence leaf development in P. alba.